Expanding traditional tendon-based techniques with nerve transfers for the restoration of upper limb function in tetraplegia: a prospective case series. Issue 10198 (17th August 2019) - van Zyl, Natasha; Hill, Bridget; Cooper, Catherine; Hahn, Jodie; Galea, Mary P
Summary: Background: Loss of upper extremity function after cervical spinal cord injury greatly affects independence, including social, vocational, and community engagement. Nerve transfer surgery offers an exciting new option for the reanimation of upper limb function in tetraplegia. The aim of this study was to evaluate the outcomes of nerve transfer surgery used for the reanimation of upper limb function in tetraplegia. Methods: In this prospective case series, we consecutively recruited people of any age with early (<18 months post-injury) cervical spinal cord injury of motor level C5 and below, who had been referred to a single centre for upper extremity reanimation and were deemed suitable for nerve transfer. All participants underwent single or multiple nerve transfers in one or both upper limbs, sometimes combined with tendon transfers, for restoration of elbow extension, grasp, pinch, and hand opening. Participants were assessed at 12 months and 24 months post-surgery. Primary outcome measures were the action research arm test (ARAT), grasp release test (GRT), and spinal cord independence measure (SCIM). Findings: Between April 14, 2014, and Nov 22, 2018, we recruited 16 participants (27 limbs) with traumatic spinal cord injury, among whom 59 nerve transfers were done. In ten participants (12 limbs), nerve transfers were combined with tendon transfers. 24-month follow-up data were unavailable for three patients (five limbs). At 24 months, significant improvements from baseline in median ARAT total score (34·0 [IQR 24·0–38·3] at 24 months vs 16·5 [12·0–22·0] at baseline, p<0·0001) and GRT total score (125·2 [65·1–154·4] vs 35·0 [21·0–52·3], p<0·0001) were observed. Mean total SCIM score and mobility in the room and toilet SCIM score improved by more than the minimal detectable change and the minimal clinically important difference, and the mean self-care SCIM score improved by more than the minimal detectable change between baseline and 24 months. Median Medical Research Council strength grades were 3 (IQR 2–3) for triceps and 4 (IQR 4–4) for digital extensor muscles after 24 months. Mean grasp strength at 24 months was 3·2 kg (SD 1·5) in participants who underwent distal nerve transfers (n=5), 2·8 kg (3·2) in those who had proximal nerve transfers (n=9), and 3·9 kg (2·4) in those who had tendon transfers (n=8). There were six adverse events related to the surgery, none of which had any ongoing functional consequences. Interpretation: Early nerve transfer surgery is a safe and effective addition to surgical techniques for upper limb reanimation in tetraplegia. Nerve transfers can lead to significant functional improvement and can be successfully combined with tendon transfers to maximise functional benefits. Funding: Institute for Safety, Compensation, and Recovery Research (Australia).